Comparison of multilevel inverters with T-type MLI: A brief review - Lakshmi, G. Sree; Kumar, S. Naveen (Penerbit Universiti Kebangsaan Malaysia, 2023)
This paper gives a comparative analysis of different types of Multilevel Inverters with T-Type inverters. The principal aim of the work is to analyse the T-type multilevel inverter operation with different multilevel inverters such as Diode-Clamped Multilevel Inverter, Flying Capacitor Multilevel Inverter and Cascaded H-bridge Multilevel Inverter. All the inverters are compared and their advantages, disadvantages and usages are specified. The inverter used in our work runs on the multilayer bidirectional DC-DC converter. This can be used in Renewable Energy Sources and Electric Vehicle applications. The proposed design includes two power switches with an additional capacitor to balance the currents of the multilayer T-type (MLI) capacitor during an entire drive pattern or fault circumstances. In this design, the big capacitors being electrolytic in T-type Multilevel Inverter has been exchanged with longer-lasting film capacitors due to the high-frequency cycle-by-cycle current security between CN and CP. The converter’s dimensions and weight would be lowered by 20% because of this topology, as the number of switches and the capacitors used for balancing is reduced in this proposed design. The simulation analysis for five-level conventional T-type inverter and proposed T-type inverter with capacitor voltage balancing is done. The line-to-line voltages, line currents, phase voltages, three-phase voltages, and voltage total harmonic distortions are compared for conventional T-type inverter and proposed T-type inverter with capacitor voltage balancing. The simulation results shows that the proposed T-type inverter gives better performance compared to conventional T-type multilevel inverter.